2011
DOI: 10.1002/adfm.201101053
|View full text |Cite
|
Sign up to set email alerts
|

Versatile α,ω‐Disubstituted Tetrathienoacene Semiconductors for High Performance Organic Thin‐Film Transistors

Abstract: Facile one‐pot [1 + 1 + 2] and [2 + 1 + 1] syntheses of thieno[3,2‐b]thieno[2′,3′:4,5]thieno[2,3‐d]thiophene (tetrathienoacene; TTA) semiconductors are described which enable the efficient realization of a new TTA‐based series for organic thin‐film transistors (OTFTs). For the perfluorophenyl end‐functionalized derivative DFP‐TTA, the molecular structure is determined by single‐crystal X‐ray diffraction. This material exhibits n‐channel transport with a mobility as high as 0.30 cm2V−1s−1 and a high on‐off rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 83 publications
(50 citation statements)
references
References 61 publications
0
50
0
Order By: Relevance
“…[ 27,28 ] Recently, many research groups have reported that the presence of fused thiophene units in π -conjugated oligomers is an effective means of invoking strong intermolecular interactions and improving environmental stability. [29][30][31][32][33] …”
Section: Resultsmentioning
confidence: 99%
“…[ 27,28 ] Recently, many research groups have reported that the presence of fused thiophene units in π -conjugated oligomers is an effective means of invoking strong intermolecular interactions and improving environmental stability. [29][30][31][32][33] …”
Section: Resultsmentioning
confidence: 99%
“…This hole fi lling of trap states can sometimes lead to higher fi eld-effect mobilities. [ 29 ] data ( Figure 7 ), thereby suggesting a plausible reason for the reduced carrier mobility observed for BBTDT versus P-BTDT , despite the fact that the larger BBTDT π -core relative to the other BTDT molecules is expected, all other things being equal, to increase the electronic interaction between π orbitals of adjacent molecules, [ 22 ] and to decrease the Marcus reorganization energy. [ 27 , 28 ] The case of PF-BTDT is unique in that the thin fi lm structure does not correlate with the bulk single crystal structure.…”
Section: Organic Thin-film Transistor (Otft) Characterizationmentioning
confidence: 97%
“…However, PF-BTDT exhibits a 5% weight loss temperature ≈ 247 ° C, lower than that of P-BTDT , indicating higher volatility due to the fl uorocarbon substitution. [ 22 ] The optical absorption spectra of Bp-BTDT , Np-BTDT , and BBTDT in o -C 6 H 4 Cl 2 solution (Supporting Information Figure S1) are slightly red-shifted ( λ max > 369 nm), relative to that of the P-BTDT ( λ max ≈ 358 nm). In contrast, the absorption spectrum of PF-BTDT is slightly blue-shifted relative to P-BTDT .…”
Section: Thermal Optical and Electrochemical Properties Of Btdt Dermentioning
confidence: 98%
“…Despite the excellent performance of fused-thiophenes in OTFTs [61][62][63][64][65][66], fused-thiophene-based OPV and DSSC studies are still in their infancy. It is well known that there are a number of factors determining the efficiency of the photovoltaic cells, and that the multiparameter problem remains to be solved.…”
Section: Discussionmentioning
confidence: 99%